Personality Competence of Arabic Language Teachers From the Perspective of Islamic Educational Philosophy - Isop Syafei; Rohanda Rohanda (Gunung Djati Conference Series, 2025)
The purpose of this study is to conduct an in-depth examination of the personality competence of Arabic language teachers based on the principles of Islamic educational philosophy. This research employs a qualitative approach with a literature study method to analyze the personality competence of Arabic language teachers from the perspective of Islamic educational philosophy. Primary and secondary data were collected from classical and modern literature, including the works of al-Ghazali and policy documents. Data collection techniques involved document review and evaluation of sources based on their credibility and relevance. Data analysis was conducted using descriptive-analytical content analysis to interpret meanings and patterns within the texts, resulting in a profound philosophical understanding of the personality competence of Arabic language teachers. The findings indicate that Islamic educational philosophy positions Arabic language teachers as moral exemplars and spiritual guides. Personality competence encompasses tauhid (the oneness of God), moral integrity, emotional balance, professionalism, cultural wisdom, and commitment to spiritual development. By integrating Qur’anic values and language skills, teachers play a strategic role in shaping students’ faith, morality, and competencies, thereby making education holistic, relevant, and beneficial for the welfare of the community. These findings affirm that Arabic language teachers must develop personality competencies including tauhid, moral integrity, emotional balance, professionalism, cultural wisdom, and spiritual commitment. This is essential to realizing Arabic language learning that is holistic, meaningful, and aligned with the values of Islamic educational philosophy for the betterment of society.